ANALISIS DAMPAK PEREKONOMIAN DI INDONESIA DALAM PANDEMIC COVID-19 - Martini, Martini; Sari, Desmita Puspa (LPPM UNIVERSITAS BINA INSAN, 2021)
The world was shocked by the phenomenon at the beginning of 2020, the Covid-19 Pandemic, it was known that the case came from the city of Wuhan, China. China identified the case on January 7, 2020 as a new type of Coronavirus. The impact of the Covid-19 pandemic will impact the global economy. China is the second largest country affected by Covid-19 in the world. Last year, China's economic growth was 6.1% and decreased by 3.8% this year. If the situation continues to decline, economic growth in China could reach 0.1% and even reach minus numbers. Credible research institutes in the world have predicted the world economy will hit the world. In March 2020, the Indonesian Government has carried out handling in response to the Covid-19 Pandemic Case, namely Social Distancing, Physical Distancing. In this policy, the community does not comply with it properly because of the lack of awareness that the community has about this case. Then a new policy was implemented, namely PSBB (Large-Scale Social Restrictions) for a relatively long period of time. Some offices and most industries are prohibited from operating. The impact of this policy causes economic losses.